INTO THE WILD: ORANGUTAN CONSERVATION CENTER IN SEI GOHONG, PALANGKARAYA AS EDU-ECOTOURISM - Ananda Rizki Puteri, Lidhiya
In the midst of the conservation efforts for Bornean Orangutans, there are Orangutans that fail to return to the wild, known as Unreleasable Orangutans. Unreleasable Orangutans are important research subjects, but unfortunately, they pose challenges regarding funding and space availability. This project aims to provide facilities that support a comfortable and secure life for Unreleasable Orangutans throughout their remaining years. To achieve this main goal, the project is directed towards having healthcare and research facilities to directly support species sustainability, as well as education and tourism facilities to contribute to long-term conservation efforts. It is hoped that this project can assist in preserving Orangutans and educating humans about the importance of protecting this species. The project, located in Palangkaraya, Central Kalimantan, has three design issues and one main concept. The design issues of this project are derived from various aspects that influence long-term orangutan conservation activities: The need of proper facilitates to support conservation activities. The need of space that can support the act of transfer education to preserve nature, and the need of design that stimulates interest in nature. To address these issues, the design incorporates a main concept that invites users to go through a sequence of spatial experiences that inspire them to understand, learn, and together preserve nature. This main concept is then divided into three aspects: a design centered around the comfort and safety of orangutans, a design that raises awareness and educates, and a design that captures visitors' attention towards nature. The building is designed with the intention of showcasing nature and its surrounding context. It is created to complement and blend with the natural environment. The placement of the building follows the organic shape of the site plan while also considering the local building techniques and technology. The main symbol of the area, the reception building, is planned to reflect the local culture and technology. The research building, located closest to the orangutan habitat, is designed to seamlessly integrate with nature, employing an underground structure and utilizing vegetation to camouflage it from the orangutans. The circulation for visitors is distinct from the circulation for the staff, taking into account space efficiency, which results in the creation of a skywalk made of perforated metal.